Pengaruh Pengangguran dan Pendidikan Terhadap Kemiskinan di Provinsi Sumatera Utara (Lembaga Pengembangan Kinerja Dosen, 2025)
Poverty is a complex and deep social problem, which affects various aspects of people's lives, from health, education, to economic prosperity. This study aims to determine the impact of unemployment and education on poverty in North Sumatra Province. The analysis method uses OLS (Ordinary Least Square) using the Eviews 12 analysis tool. The data in this study uses secondary data sourced from the North Sumatra Central Statistics Agency. The study results show that unemployment has a positive impact on poverty. Meanwhile, education has a negative impact on poverty found in North Sumatra Province.